(3dHGH GdefGSc hYHGH GdeSGdcs - (3GdSfOj, QMeI Gddg Hf YHO Gddg Hf EHQGgje, J (B993 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Cced GdMeO Ydi eG gOGfG ddGSdGe HGH TQhW GdML ; GdML aQV eQI HGdELeGY Ydi cd ef GSJLeY ajg GdTQGFW hgj CfhGY ; GdfhY GdChd TQGFW GdhLhH , GdChd efgG GdESdGe adG jLH Ydi cGaQ hdG jUM efg s
(3BNQgG (B:s
(3haVd RjGQI NjQ qeRhQ Cfg jYhO NjQG eeG cGf aj LejY GdCehQ , aZf QCi aj faSg fRhYG Yf GdCHGWjd hJLGajG Yf OGQ GdZQhQ hEfGHI Edi OGQ GdNdhO hHg jJe dHGH GdeQGes
(3JHUQI GdYfhGf (B:s
(3dNUg GdeDda ef cJGHg aj LeY GdefGSc (B( (3eLGeY GdefGSc hfaY GdfGSc(B)s
(3JHUQI GdeDda (B:s
(3eDPf GdMfajIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B3\19s
Keywords: (3Gdabg GdMfajs